2017
DOI: 10.1088/1742-6596/830/1/012130
|View full text |Cite
|
Sign up to set email alerts
|

Using Rouse-Fowler model to describe radiation-induced electrical conductivity of nanocomposite materials

Abstract: Abstract. Using the Rouse-Fowler (RF) model this work studies the radiation-induced electrical conductivity of a polymer nanocomposite material with spherical nanoparticles against the intensity and exposure time of gamma-ray, concentration and size of nanoparticles. The research has found the energy distribution of localized statesinduced by nanoparticles. The studies were conducted on polymethylmethacrylate (PMMA) with CdS nanoparticles. IntroductionNanocomposite materials are materials formed by inclusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We showed [12], that the values of radiation induced electrical conductivity calculated by this method are in the good agreement with results obtained by other authors.…”
Section: Mathematical Modelsupporting
confidence: 90%
See 4 more Smart Citations
“…We showed [12], that the values of radiation induced electrical conductivity calculated by this method are in the good agreement with results obtained by other authors.…”
Section: Mathematical Modelsupporting
confidence: 90%
“…Previously, we showed that the ionization of inclusion has the contribution to the ionization of nanocomposite materials, comparable with the ionization of matrix material [12].…”
Section: Mathematical Modelmentioning
confidence: 80%
See 3 more Smart Citations